Local Ecological Knowledge of Coffee Farmers on Earthworms and Pests as Soil Quality in Mount Tambora, Indonesia - Gading, Wira; Hairiah, Kurniatun; Rizali, Akhmad (Universitas Panji Sakti, 2025)
The local ecological knowledge of coffee agroforestry farmers regarding earthworms serves as one of the soil fauna indicators of soil fertility and quality. This knowledge is inherited through generations from observations and experiences of coffee farmers, sometimes differing from modern ecological knowledge. This study aims to analyze the relationship between farmers Local Ecological Knowledge (LEK) in simple coffee agroforestry systems and their socio-demographic characteristics; to examine their understanding of the ecological roles of earthworms and Lepidiota stigma; and to identify and assess the gap between Local Ecological Knowledge (LEK) and Modern Ecological Knowledge (MEK). Local ecological knowledge was obtained through in-depth interviews with coffee agroforestry farmers concerning soil management, the role of earthworms, and pests in maintaining soil quality on the slopes of Mount Tambora (NTB). In-depth interviews were conducted with key respondents and coffee agroforestry farmers grouped by gender, age, and educational background using predetermined questions. Based on interviews with 50 coffee farmers, the percentages of soil quality indicators recognized by them ranked as follows: earthworms (80%), soil color (74%), plant growth (36%), humus or litter (10%), and soil structure (6%). Furthermore, 72% (n=50) of coffee farmers indicated that soil organisms significantly influence soil fertility. This study highlights the scientific value of Local Ecological Knowledge in sustainable soil management and encourages its integration with modern science through participatory research.